STATUS HAK WAKAF YANG TIDAK SESUAI DENGAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 41 TAHUN 2004 TENTANG WAKAF DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Sy. Khairol Olfa; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Law of the Republic of Indonesia Number 41 Year 2004 on Waqf regulate and protect the perwakafan in Indonesia, but the habits of the people Subdistrict Mandah in perwakafan done orally and by letter that was made between wakif and nadzir is not done according to orders legislation on waqf requires Parties donating land to be pledged his will clearly and firmly to the front nadzir endowment Deed official Pledge so how the status of waqf land rights that done outside the provisions of regulations tersebutpun in question. As for the purpose of this thesis, namely: First, the transfer of rights to know dikecamatan mandah waqf land. Second, to find out the status of waqf rights that are not in accordance with the Waqf Act. Third, To Know solution that can be done to overcome the problems regarding the status of rights of endowments that are inconsistent with the Act of Endowment. This research is sociological research that want to see the unity between law and society with the gap between sollen and das das sein. The research was conducted in the District Mandah District Inderagiri Downstream, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this research is done through interviews and review of the literature.The conclusion that can be obtained from this study is the first, implementation of transfer of rights on waqf land in District Mandah there are still people in perwakafan Habits are done with oral and certificate made between wakif and nadzir without front Deed Official Pledge. Second, the status of waqf land that is not done through the deed of pledge endowment before PPAIW have the strength of evidence is not perfect in view of the legislation perwakafan make the non-recognition of legal acts perwakafan the Third, the solution can be done that If wakif still alive then the solution is to endowment Deed of Pledge made by PPAIW, On wakif who had died solutions that can be done is to be made waqf Deed in Lieu Deed of Pledge (APAIW) and if there sangketa, nadzir can apply for the establishment of endowments to the Religious Courts.Advice authors to the issues examined are the First, Preferably the active role which government, represented by the Office of Religious Affairs to be the initiator gives more attention in the management of waqf property. Second, to improve the future of public awareness of the need legal counseling to every citizen. Thirdly, To the community, especially dikecamatan mandah pengikraran for more attention to the importance of endowments in the presence of Waqf Deed Official Pledge.Key Words: Status Rights Endowments - Unsuitable OF legislation